Listed : dispatches from America's Endangered Species Act - Roman, Joe, 1963- (Harvard University Press, 2011)
A lot has changed since the 1970s, when the tiny snail darter went extinct on the Little Tennessee River. Joe Roman helps us understand why we should all be happy about the sweeping law that made these changes possible. "Listed "is an engaging tale of endangered species in the wild and the people working to save them.